Desenvolvimento de um sistema de apoio automatizado para gestão eficiente de auxílios estudantis na UFC – Campus Sobral - Sousa, Igor Maciel de (2025)
The administrative processes of student assistance have a significant impact on students’ lives, as the decisions made directly influence access to benefits such as scholarship programs. Currently, a large portion of these processes is still carried out manually, making them time-consuming and prone to errors, in addition to overburdening the assistants responsible for data analysis. To optimize this management, this work proposes the development of a desktop system to automate and facilitate the administration of student aid at the Federal University of Ceará, Sobral campus. The choice of a desktop system is due to the need to restrict access only to authorized computers within the local network, ensuring greater control and security over the data. Unlike a web system, which can be accessed from the server machine’s IP address and allows page manipulation through browser tools such as the element inspector, the desktop system provides an additional layer of protection against unauthorized access and improper modifications to the interface. The system enables the importation of students’ socioeconomic data from CSV files, automatically populating an interactive interface that allows individual and bulk editing, filtering, column hiding, dynamic search, pagination, and data export in different formats. Additionally, the system generates detailed reports and applies objective criteria for student selection based on a weighted sum formula defined by PRAE, ensuring transparency and agility in the decision-making process. The system was developed using the Python programming language, with PyQt as the main library for the graphical interface. Data manipulation and analysis are handled using the Pandas and NumPy libraries, while information storage is managed by a MySQL database. With this approach, the system aims to reduce the time spent on data analysis, minimize errors, and provide a more efficient and accessible management of student assistance. Furthermore, centralizing the data in the database ensures greater integrity, security, and consistency of the information, allowing future analyses to be more accurate and comprehensive, facilitating strategic decision-making based on consolidated data.